Effects of international climate policy for India: Evidence from a national and global CGE model - Matthias Weitzel; Joydeep Ghosh; Sonja Peterson; Basanta Pradhan (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In order to reach the two degree target it is necessary to control CO2 emissions also in fast growing emerging economies such as India. The question is how the Indian economy would be affected by e.g. including the country into an international climate regime. Existing analyses with either a global model or a single country computable general equilibrium model miss important aspects such as distributional issues or international repercussions. By soft-linking models of these two classes, we provide a more detailed view on these issues. In particular, we analyze different options of transferring revenues from domestic carbon taxes and international transfers to different household types and how different assumptions on exchange rates affect transfer payments. We also show effects stemming from international price repercussions. Our analysis focusses on how these transmission channels affect welfare of nine different household types.
Keywords: C68; Q54; Q56; 330